Dynamic modelling and analysis of a coal-fired power plant integrated with a novel split-flow configuration post-combustion CO capture process - Mac,Dowell N; Shah,N (International Journal of Greenhouse Gas Control, 2014)
We present a model of a coal-fired power plant integrated with a dynamic model of a monoethanolamine (MEA)-based post-combustion CO capture process. We evaluate base- and part-load operating modes of the integrated power and CO capture plant. We propose a simple modification to the base-process which exploits the tradeoff between thermodynamic and rate or kinetic driving forces for mass transfer. This modification returns a portion of the regenerated solvent to the middle of the absorption column at an elevated temperature. Under base-load operation of the power plant, this modification was observed to increase the degree of CO capture by 9.9% and reduce the reboiler duty by 8.3%, improving the net electrical efficiency of the decarbonised power plant from 28.27% to 29.15% - a relative increase of 2.8%. Under part-load operation, the degree of CO capture increased by 1% with a concurrent reduction in reboiler duty of 16.7% and an increase in overall process efficiency of 3.25%